2018
DOI: 10.1080/03007995.2018.1476333
|View full text |Cite
|
Sign up to set email alerts
|

Initial combination therapy with vildagliptin plus metformin in drug-naïve patients with T2DM: a 24-week real-life study from Asia

Abstract: Overall, in a relatively young drug-naïve T2DM Asian study population with high baseline HbA1c and often associated with cardiovascular risk factors, vildagliptin/metformin combination therapy was associated with significant and clinically relevant HbA1c reduction from baseline. This effect was seen at week 12, was maintained over 24 weeks, and was accompanied by good tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…As the risk of hypoglycemia is more often associated with weight gain, previous studies reported no weight gain with vildagliptin metformin therapy. [ 17 19 20 ] This is confirmed by the present study findings. However, the mean body weight was comparable between both the groups at 6-weeks and 12-weeks follow-up.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As the risk of hypoglycemia is more often associated with weight gain, previous studies reported no weight gain with vildagliptin metformin therapy. [ 17 19 20 ] This is confirmed by the present study findings. However, the mean body weight was comparable between both the groups at 6-weeks and 12-weeks follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…The initial combination therapy with vildagliptin and metformin was well tolerated in these patients associated with high HbA1c and cardiovascular risk factors. [ 17 ] This attributed to glucose-dependent nature of vildagliptin with insulinotropic polypeptide-mediated effect that helps to lower the incidence of hypoglycemia. [ 18 ] Moreover, vildagliptin has weight neutral activity.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 The INITIAL study and VERIFY trial based studies demonstrated that early combination therapy (vildagliptin plus metformin) provided better glycemic control than initial metformin monotherapy for T2DM patients. 11–14 However, there exist a lacuna of real-world data based evidence wherein the comparative effectiveness of combination therapy and monotherapy has not been assessed in real-world Indian settings. This evidence will aid the treating clinicians in decision making to provide the individualized and holistic care to the patients for better diabetes management.…”
Section: Introductionmentioning
confidence: 99%
“…The Initial combiNation therapy with vildagliptin plus metformin In drug-naïve T2DM patients In a reAl Life setting (INITIAL) study demonstrated significant reductions in Hb A1c both at weeks 12 and 24 (−1.6% and −1.9%, respectively; p < 0.001) after initial treatment with vildagliptin–metformin combination in Asian patients with T2DM who presented with high baseline HbA1c (9.3% ± 1.6%) and multiple CV risk factors [ 26 ].…”
Section: Clinical and Real-world Benefits Of The Metformin Sr–vildagl...mentioning
confidence: 99%